ADAPTASI KOMUNIKASI BUDAYA MAHASISWA ASING DI UNIVERSITAS NEGERI SURABAYA - Listrikasari, Dian Rahmadani; Huda, Anam Miftakhul (Universitas Negeri Surabaya, 2024)
Universitas Negeri Surabaya is affiliated with such scholarships for foreign students for studying in Indonesia, affording them the opportunity to pursue similar academic programs as their domestic counterparts. However, this situation may lead to culture shock for international students. Culture shock was first introduced by Oberg in 1960 to describe the profound and negative response of depression, frustration, and disorientation experienced by individuals living in a new or different cultural environment from their place of origin. Samovar (2015) also suggests that the phenomenon of culture shock parallels someone feeling exhausted after engaging in various activities in a new environment that consume time, mental effort, and energy beyond what was anticipated. This research endeavors to gather and analyze the adaptation process of foreign students at Universitas Negeri Surabaya, aiming to identify the challenges and factors that affect the adaptation process. The study employs interview methods to capture the experiences of foreign students at Universitas negeri Surabaya. Using Samovar et al.'s (2015) culture shock theory, the research seeks to delineate the stages of culture shock experienced by students, identifying obstacles, and exploring the various strategies they employ to address these challenges. With using a qualitative phenomenological approach, the study seeks to provide a comprehensive understanding of the cultural communication adaptation of foreign students.